MR Imaging of Congenital or Developmental Neuropathic Strabismus: Common and Uncommon Findings - Kim, E.; Kim, J.H.; Hwang, J.M.; Choi, B.S.; Jung, C. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: High-resolution MR imaging enables direct imaging of the ocular motor nerves. The aim of this study was to assess the various causes of congenital or developmental neuropathic strabismus by using high-resolution MR imaging. MATERIALS AND METHODS: High-resolution MR imaging was performed to evaluate the ocular motor nerves (CNIII, CNIV, CNVI) in 247 consecutive patients with suspected congenital or developmental neuropathic strabismus. These MR images, along with those obtained from conventional MR imaging of the brain and the orbit, were evaluated. RESULTS: MR imaging abnormalities were found in 112 patients: ocular motor nerve abnormalities in 98 patients (88%), orbital abnormalities in 9 patients (8%), and brain abnormalities in 5 patients (4%). Ocular motor nerve abnormalities were CNIV aplasia (63%), CNVI aplasia or hypoplasia (21%), CNIII aplasia or hypoplasia (3%), and combined CNIII aplasia and CNVI hypoplasia (1%). Orbital abnormalities were EOM hypoplasia (7%), EOM hypertrophy (1%), and fibrotic mass (1%). Brain abnormalities were periventricular leukomalacia (4%) and periventricular heterotopia (1%). CONCLUSIONS: Various MR imaging abnormalities were associated with congenital and developmental neuropathic strabismus. The most common abnormality was CNIV aplasia. CNcranial nerveEOMextraocular muscleSENSEsensitivity encoding3D-bTFE3D balanced turbo-field echo